The Impact of Covid-19 on the Implementation of Online Learning at SDN Jenggot for the 2020 Academic Year - Erlina Listiyanti; Delia Indrawati (Universitas PGRI Adi Buana Surabaya, 2022)
This study was to find out how the implementation of the online learning model is, the inhibiting factors for the implementation of online learning and also to find out the supporting factors for the implementation of online learning during the Covid-19 pandemic in elementary schools. Online learning requires teachers to prepare learning that is more creative than ordinary learning when offline, because it requires special skills in terms of technology and adaptation to remote situations with students. The type of research used is a type of qualitative research. The focus of this research is on the impact of Covid-19 on the implementation of online learning. The research location is at SDN Jenggot, Krembung District, Sidoarjo Regency. The interview respondents were a total of 6 including teachers and students who were involved to strengthen the results of the interviews. Data collection techniques using literature review methods, observations and interviews. As for the validity of the data using data manipulation techniques so that the data is believed to be a truth or fact. The data analysis technique uses descriptive data in compiling research data so that it can be concluded that this study shows that teachers have different standards of success with other teachers, while the causative factors include age which is difficult to adapt to technology. Meanwhile, other junior teachers are easy to adapt to the online learning process. Teachers who apply online learning are able to operate devices and software that support online learning.